An experimental study of the behaviour of delaminations in composite panels subjected to bending. (May 2015) - Gong, Wenran; Chen, Jinlong; Patterson, Eann A.
Abstract: Delamination is one of the most common forms of damage suffered by laminated composites and often occurs as a consequence of manufacturing defects or an impact. This paper reports an investigation of the buckling behaviour and resultant damage modes in delaminated composites subjected to four-point bending. The stereoscopic Digital Image Correlation (DIC) method was used to measure full-field deformations and to evaluate maps of surface principal strains in Carbon Fibre-Reinforced Plastic (CFRP) laminates with artificial delaminations. The effect of delamination size and shape on buckling behaviour was investigated using circular and elliptical delaminations in thin beams under four-point bending. For circular delaminations, initially the delamination grew along the transverse direction and then changed to the longitudinal direction. For elliptical delaminations, the delamination grew only along the longitudinal direction. Furthermore, the orientation of the delamination had a small influence (10–15%) on the critical delamination-buckling load, which decreased with increasing ratio of minor to major axis length of the delamination.